Soursop contamination and sprouting in function of the fungicide in the culture medium - De Andrade, Renata Aparecida [UNESP]; Bagatim, Amanda Garcia [UNESP]; Jasper, Samir Paulo (My University, 2014)
The present research was conducted to verify the effectiveness of adding different doses of fungicide to the culture medium, in the contamination of in vitro culture of the explants of soursop. The experiment was conducted using explants collected from seedlings of soursop that were kept on lath house conditions (50% brightness), underwent three treatments, consisting in doses of fungicide carbendazim added to the MS culture medium: 5 ml per liter of culture medium, 10 ml/L, 15 mL /L, more a control treatment. The study lasted for 42 days and were evaluated daily number of explants with contamination and with budding. There was no beneficial effect of fungicide in reducing contamination, nor in increased sprouting, for the in vitro cultivation of soursop.
Keywords: Annona muricata L.; Carbendazim; In vitro propagation